The Bhagavad Gita as a Framework for Sattvic AI: Aligning Artificial Intelligence with Sustainable Development - Adhikari, Shiva Raj; Shrestha, Hira Lal; Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2026)
Background: The current "move fast and break things" approach to technology and innovation is proving to be a significant threat to humanity, especially when artificial intelligence (AI) is considered to be a civilization-altering technology. In the absence of a robust ethical foundation, AI could potentially worsen the current sustainability crises and hinder the achievement of the United Nations Sustainable Development Goals (SDGs). The current state of AI ethics, where sustainability is considered a secondary principle, points to a critical need to develop foundational and value-based approaches.Objective: This article aims to bridge the current gap between the technological advancement of artificial intelligence and sustainability wisdom. It aims to develop a new and unique ethical framework for sustainable artificial intelligence development based on the philosophical concepts of the Bhagavad Gita.Methods: This article uses a conceptual synthesis to apply three of the fundamental concepts of the Bhagavad Gita to the artificial intelligence development process: Dharma (Cosmic Duty) to redefine artificial intelligence's purpose; Nishkama Karma (selfless action) to discipline artificial intelligence development; and the three gunas of Sattva, Rajas, and Tamas to evaluate artificial intelligence's impact.Analysis: The synthesis creates a pathway to a new form of "Sattvic AI" – technology that promotes balance and regeneration. It offers a set of tools to support its implementation, including a Dharma Statement to inform purpose, Nishkama Development Protocols to ensure ethical development, and a Guna Impact Assessment (GIA) to measure success in relation to the SDGs.Conclusion: The principles of the Bhagavad Gita offer a rich and profound philosophy upon which to base a transformation in the use of AI from a force of exploitation to one of world welfare (Lokasamgraha). The proposed pathway offers policymakers and developers a tangible means to create an AI that not only does not hinder, but actually supports, sustainable development.Novelty: The paper offers the first application of Bhagavad Gita philosophy to create a structured and operational pathway to support the development of ethical and sustainable AI.